(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2017)
Wheat straw was modified with malonic acid in order to get low cost adsorbent have a good ability to remove copper and ferric ions from aqueous solutions, chemical modification temperature was 120°C and the time was 12 h. Parameters that affect the adsorption experiments were studied and found the optimum pH were 6 and 5 for copper and iron respectively and the time interval was 120 min and the adsorbent mass was 0.1 g. The values for adsorption isotherms parameters were determined according to Langmuir [qmax were 54.64 and 61.7 mg/g while b values were 0.234 and 0.22 mg/l] , Freundlich [Kf were 16.07 and 18.89 mg/g and n were 2.77 and 3.16], Temkin [B were 0.063 and 0.074 j/mol and At were 0.143 and 1.658 l/g] and for Dubinin-Radushkevich [Kad were 3*106- and 9*107- , qs were 48.42 and 44.70 mg/g, E were 0.408 and 0.745 Kj/mol] for copper and iron ions respectively. The adsorption for both ions are physical since the n values in Freundlich were more than 1, the mean of free energy for Dubinin-Radushkevich were 0.408 and 0.745 Kj/mol and B values for Temkin equation B were 0.063 and 0.074 j/mol.